«De la noncin» et «d'une nonne». Lecture cnmparée des structures spatiales dans les miracles - Loba, Anna (Studia Romanica Posnaniensia, 2001)
The paper is a comparison of the two narrative and dramatic medieval miracles. The texts come from different times, but they both, tell the same story - a miraculous intervention of the Virgin Mary on a life of a young nun. Written in the 14th century, the dramatic version is an adaptation of Gautier de Coincy narrative miracle. The author of the paper intends to seize the spatial transformations that occur between narrative “hypotexte” and dramatic “hypertexte”. Indirectly, this analysis evokes a question of rewriting in French medieval literature.